Evaluation of Renal Function in Pregnant Women with Malaria: A Case-Control Study in a Mesoendemic Area - Justice Afrifa; Samuel Essien-Baidoo; Albert Baffour Gyau; Richard Kobina Dadzie Ephraim (Hindawi Limited, 2017)
Background. Malaria is known to have devastating effects on mortality in tropical and subtropical regions with the effect being magnified in people with weakened immunity such as those in pregnancy. We assessed the effect of malaria on renal function of pregnant women receiving antenatal care in a mesoendemic area of Ghana. Methodology. A case-control study that enrolled a total of 100 pregnant women (50 with confirmed gestational malaria as cases and 50 without malaria as controls). Sociodemographic characteristics, obstetric history (obtained with a questionnaire), urea, creatinine, sodium, and potassium were analyzed using a chemistry automated analyzer. Results. Plasma urea and creatinine were significantly increased (P=0.0003 and P<0.0001, resp.) among cases compared to the controls. Also the levels of urea (P=0.033), creatinine (P=0.032), and parasitaemia (0.016) were significantly increased with increasing gestational age. Conclusion. Malaria has a significant impact on renal function (most importantly, urea and creatinine) and is also significantly associated with increasing gestational age among our study participants.